Qualidade de maçãs armazenadas em atmosfera controlada dinâmica com diferentes níveis de CO2 e em níveis extremamente baixos de oxigênio com estresses periódicos por hipoxia através de diferentes histereses - Schultz, Erani Eliseu (2021)
The storage of apples in a dynamic controlled atmosphere (DCA), where the low oxygen limit (LOL) is monitored, allows the use of extremely low levels of oxygen. Among the most studied techniques are chlorophyll fluorescence (CF) and respiratory quotient (RQ). Monitoring LOL is important to avoid excessive induction of anaerobic metabolism compounds caused by excessive O2 reduction. The study of the effect of different partial pressures of CO2 on extremely low levels of O2 in DCA is important in order to provide improvements in fruit conservation and a reduction in the cost of CO2 absorption in the chambers. Furthermore, the adoption of extremely low static O2 levels and the hysteresis of the variation in these levels still need further studies. In this context, in the present work, three papers were developed with the aim of: [1] evaluating different pCO2 in DCA-RQ and its effect on the overall quality ‘Maxi Gala’ apples after 9 months of storage plus 7 days of shelf life, in addition, compare with controlled atmosphere with application of 1-methylcyclopropene (1-MCP) and DCA-CF; [2] evaluate the effect of CO2 levels in DCA-RQ on the overall quality and volatile profile of apples after 9 months of storage plus 21 days of shelf life and compare with CA +1-MCP and DCA-CF and [3] study the effect of storage at extreme low oxygen levels (ELO) with induction of stresses by low O2 (hysteresis) on the overall quality and emission of volatile compounds after 9 months of storage plus 7, 14 and 21 days of shelf life, and compare them with CA + 1-MCP, DCA-CF and DCA-RQ. The storage of ‘Maxi Gala’ apples during 9 months in DCA-RQ 1.3 with 1.6 and 2.0 kPa of CO2 plus 7 days of shelf life maintains fruit quality similar to DCA-RQ 1.3 with 1.2 kPa of CO2. DCA-RQ 1.3 with 1.2 and 1.6 kPa CO2 maintains high fruit quality after 9 months of storage plus 21 days of shelf life at 20 °C. Storage in DCA-RQ 1.3 with 0.4 kPa CO2 maintains a high percentage of healthy fruit, but reduce flesh firmness during the entire shelf life (21 days). DCA-RQ 1.3 with 2.0 kPa CO2 maintains similar fruit quality to DCA-RQ 1.3 with 1.2 and 1.6 kPa CO2 up to 14 days of shelf life. DCA-QR 1.3 with 1.2, 1.6 and 2.0 kPa of CO2 result in higher emission of volatiles (mainly esters), at 21 days of shelf life, with no difference for CA. Storage at ELO levels with or without hysteresis maintains fruit quality similar to DCA-CF, CA+1-MCP, and superior to CA after 7 days of shelf life. After 21 days of shelf life, ELO with 0.4 O2 + 0.4 and 0.6 hysteresis maintain a higher percentage of healthy fruit compared to DCA-CF, CA +1-MCP, CA and similar to DCA-RQ , but with lower flesh firmness than DCA-RQ and CA + 1-MCP. Conditions with ELO with or without hysteresis reduce the emission of the main esters, such as 2-methylbutyl acetate and ethyl acetate (with the exception of butyl acetate) at 7 and 14 days, but with an increase at 21 days. DCA-CF and CA + 1-MCP have low emission of volatile compounds during 21 days of shelf life. Apples stored in CA maintain high volatile compounds production throughout the shelf life. The results of the three works show that the storage of ‘Maxi Gala’ apple in extreme low oxygen (0.4 kPa) with hysteresis of 0.4 to 0.6 allow a better quality conservation in comparison to DCA-CF and that it is possible to increase the CO2 level to 1.6 kPa in ELO conditions , which reduce cost of electrical energy for CO2 adsorption from the CA storage room.